Validation of a modified model of TNBS-induced colitis in rats. How to induce a chemical colitis in rats - Tomasello, Giovanni; Sinagra, Emanuele; Raimondo, Dario; Palumbo, Vincenzo Davide; Puleio, Roberto; Cottone, Mario; Damiani, Provvidenza; Traina, Giovanna; Abruzzo, Alida; Damiani, Francesco; Buscemi, Salvatore; Noto, Marcello; et al. (Acta Biomedica Atenei Parmensis, 2015)
Background: There is no standard practice in the induction of colitis by 2,4,6-trinitrobenzene sulfonic (TNBS) acid. Usually, the repeated administration of TNBS is preferred, because it will result in a local Th1 response that has the characteristics of Crohn`s disease. Materials and Methods: A total of 30 rats were randomized into two groups, consisting of a saline control group of ten rats and a TNBS groups of 20 rats. After the animals were anesthetized, 0.5 ml of either 0.9% saline (controls) or TNBS 50 mg/kg dissolved in 50% ethanol were instilled into the colon through a rubber catheter. The experiment was repeated weekly for four weeks, then, the rats were killed at day 40, and the distal colon removed. Results: At day 40, the bowel wall was basically normal in the control group. In the TNBS group, the bowel lumen became narrow with thickened wall, and the mucosal surface presented adherent membrane with brown black, linear ulcers, proliferous lymphocyte tissue, inflammatory granulomas and submucosal neutrophil infiltration. The median score of the severity of the colonic damage was 0 in the control group, and 4,75 (range 4-5) in the TNBS group; the mean weight of the rats was 180+35 g in the TNBS group, while it was 215+25 in the control group. Conclusions: The presented experiment is a cost-effective and safe method to induce Crohn-like colonic damage using a lower dose of TNBS, thus avoiding the risk of a massive loss of rats. This model is rather suitable for the assessment of the effects of potential therapeutic agents. (www.actabiomedica.it)